Overexpression of Brain-Derived Neurotrophic Factor Enhances Sensory Innervation and Selectively Increases Neuron Number - LeMaster, Ann M. (J Neurosci, 1999)
Target-derived neurotrophin growth factors have significant effects on the development and maintenance of the mammalian somatosensory system. Studies of transgenic mice that overexpress neurotrophins NGF and neurotrophin 3 (NT-3) at high levels in skin have shown increased sensory neuron number and enhanced innervation of specific sensory ending types. The effects of two other members of this family, BDNF and NT-4, on sensory neuron development are less clear. This study examined the role of brain-derived neurotrophic factor (BDNF) using transgenic mice that overexpress BDNF in epithelial target tissues of sensory neurons. BDNF transgenic mice had an increase in peripheral innervation density and showed selective effects on neuron survival. Neuron number in trigeminal ganglia, DRG, and SCG were unchanged, although a 38% increase in neurons comprising the placode-derived nodose–petrosal complex occurred. BDNF transgenic skin showed notable enhancement of innervation to hair follicles as detected by PGP9.5 immunolabeling. In nonhairy plantar skin, Meissner corpuscle sensory endings were larger, and the number of Merkel cells with associated innervation was increased. In trigeminal ganglia, neurons expressing trkB receptor were increased threefold, whereas trkA-positive neurons doubled. Analysis of trkB by Northern, reverse transcription-PCR, and Western assays indicated a modest increase in the expression of the T1 truncated receptor and preferential distribution to the periphery. These data indicate that skin-derived BDNF does not enhance survival of cutaneous sensory neurons, although it does promote neurite innervation of specific sites and sensory end organs of the skin.